Dynamic Mechanical Analysis of Banyan/Ramie Fibers Reinforced with Nanoparticle Hybrid Polymer Composite - T. Raja; V. Mohanavel; M. Ravichandran; S. Suresh Kumar; Munirah D. Albaqami; Reham Ghazi Alotabi; Mohanraj Murugesan (Advances in Polymer Technology)
Natural fibers are an increasing potential alternative to synthetic fibers in recent research, due to their unique properties and weight ratio in composite materials. In this work, the banyan mat and ramie mat are used as reinforcement phase and the epoxy polymer is used as matrix material, and granite nanoparticles are used as filler for making composite laminates. The two phases of reinforcing and matrix were taken at an equal ratio of 50% in each, and the conventional hand layup process was fabricated making five different sequences of laminates. In this analysis, the dynamical mechanical properties of this hybrid composite are identified with the erratic weight ratio of banyan mat and ramie mat fabrics. The results revealed the maximum storage modulus is 1580 MPa at 93.8°C and a loss modulus of 298 MPa at 93.8°C in sample A, 12% more storage modulus, 17% more loss modulus was obtained in sample A compared to sample B, and 29% E′ and 27% E″ more compared to sample E and also using storage modulus, loss modulus, damping factor are the viscoelastic behavior which can reveal the glass transition temperature of hybrid composite laminates by conducting dynamic mechanical analysis, and SEM test was used to identify the failure mode of hybrid composite.